Knowledge, attitude, and practice of general dental practitioners towards oral biopsy procedures - Singh, Preeti; Gupta, Sujaya; Adhikari , Biplob (Journal of Kathmandu Medical College, 2023)
Background: Oral biopsies are not routinely practised by general dental practitioners (GDPs) globally. However GDPs should perform the biopsy procedures for oral lesions. The clinical and histopathological correlation is needed for the diagnosis of certain oral lesions. Objectives: To assess the knowledge, attitude, and practice of oral biopsy procedures among the GDPs. Methods: A descriptive cross-sectional questionnaire study was conducted from 2021 October to December among GDPs who were graduates of Kathmandu Medical College and registered in Nepal Medical Council. Census method was used for data collection. After institutional ethical approval, a standard questionnaire was used using Google Forms, and emailed to the GDPs (N = 72). Initial information about the study was given through the phone calls from academic section of the hospital to all the participants and follow-up was done using social media. Descriptive analysis was done using Google Sheets. Results: There was 100% response rate from the participants with predominance (45, 62.5%) of female respondents. Majority (54, 75%) of respondents were in age group of 25-29 years. Although 38 (52.8%) practitioners came across the oral lesions that needed biopsy, only two (2.8%) of them were able to perform biopsy on their own. The concept that biopsy is specialist-related procedure and lack of skill could be the main reasons for not performing the procedure. Conclusion: Majority of GDPs lack skill and confidence for performing oral biopsies. Hence, in the undergraduate dental programme itself, the priority should be given to skill-based knowledge of various oral biopsy procedures.